U.S. relations with central Asian states: A study with reference to energy resources geopolitics from 1991 to 2012 / Hujjathullah M.H. Babu Sahib - Hujjathullah M.H. , Babu Sahib (2018)

(untitled)
Though an undefined central asian region has been around historically from time immemorial, the narrowly defined Central Asia (C.A.) of the recent past was a Russian/Soviet construct of early modern vintage. In the aftermath of the Soviet demise, the region stands variously redefined, if only analytically. Hence, the Central Asian region now, as defined by this study, constitutes the states of Afghanistan, Azerbaijan, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan. The past two decades or so have witnessed the steady forging and gradual development of relations between these newly independent Central Asian states (CAS) and/or emergent republics of Central Asia (CARs) and the reviving United States of America (U.S.A.). The development of multi-sectoral relations between them betrays a subtle shift from one of apparent reluctance that characterized the early years to one of enthusiastic engagement subsequently. This study is, therefore, a research attempt to explain the nature of the evolving relations between most of the freed states of a redefined Central Asia (C.A.) and the U.S. and to account for the changes in these relationships, especially but not exclusively from late 1991 when most of these states got their independences from the erstwhile Soviet Union and found themselves, at last, left apparently free to develop their own foreign relations. Methodologically, by merely using printed and electronic materials available in the public domain, a number of pertinent variables are considered as likely causes for the development and evolution of these relations. Key among these is the importance of the region’s energy resources to the U.S. and by extension to the western countries and their other relatively energy-deficient allies. Other variables seen, in this study, as responsible for the perceived shift in relations include: American intervention in the neighboring states of Central Asia/Caspian; the varied nature of ties the Central Asian states (CAS) themselves maintain with Russia; and the consequent weakness of the U.S. in the broader C.A. convicinity. The basic objectives of this study then are: first, defining the C.A. region anew; second, accounting for the change in America’s relationships with the constituent states of this analytic region and; third, highlighting the primacy of strategic, especially energy resources in the evolution of these ties. It must be mentioned here that the present research, after surveying the region politico-geographically in broad-strokes and anchoring the entire region historically too, deliberately chooses to gloss over the internal factors in the CARs themselves, in order to give due stress to the importance of external events and the regional dynamics of the U.S.-Russian cooperation and competition, especially in regard to energy issues. After all it was these very external factors that were responsible for launching both these freed CARs and the new C.A. region too, as a relatively coherent whole in the international scene. On the whole, this study found that, in the period under review, these relationships between the U.S. and the CAS have indeed evolved and there have been changes in the nature of these ties if not also in the general direction of these relationships.